Analysis of care for cancer patients with opioid-induced constipation in clinical practice: EIO-PRAXIS Project - Enrique Aranda; Jesus Garcia-Foncillas; Antonio Anton; Carlos Camps; Alfredo Carrato; Manuel Constenla; Juan J Cruz-Hernandez; Eduardo Diaz-Rubio; Pere Gascon; Vicente Guillem; Rafael Lopez; Margarita Feyjoo; et al. (Open Journal of Pain Medicine - Peertechz Publications, 2019)
Purpose: The objective of the study was to analyses how Opioid-Induced Constipation (OIC) is managed in cancer patients in clinical practice for comparison against the current recommendations for the management of patients with OIC.